Heart-Lung Transplant via an Eighth-Time Sternotomy. Issue 1 (January 2021) - Riggs, Kyle W.; Chin, Clifford W.; Bryant, Roosevelt; Zafar, Farhan; Chin, Clifford; Schecter, Marc G.; Morales, David L. S.
We report a combined heart–lung transplantation following seven prior sternotomies in a patient born with a transitional atrioventricular septal defect. Previous surgeries to repair and replace the mitral valve led to pulmonary vein stenosis and pulmonary vascular disease. Eighth-time sternotomy and significant vascular adhesions led to a prolonged operation and to placing the heart–lung block anterior to the phrenic nerves. Despite this, the patient was ready for discharge after two weeks and continues to do well over nine months later. As more patients survive multiple cardiac palliations with some developing pulmonary vascular disease, heart–lung transplantation may become relevant again.